1970
DOI: 10.1128/iai.2.3.274-278.1970
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of Salmonella Administered Orally to Cold-Exposed Mice

Abstract: Susceptibility to enteric infection with Salmonella was studied in mice housed at different temperatures. The oral doses of S. typhimurium SR-11 and RIA, which caused 50% mortality in animals at 10 C, were about J%0 and M00 of the respective values at 23 C, and that of an avirulent strain of S. enteritidis was also lower in the cold-exposed mice. The frequency of mortality due to Salmonella infection was essentially the same in mice exposed to 34 or 23 C. The divergent responses in the cold and heat probably s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Studies dating back at least to the 1940s indicate that ambient temperature profoundly alters the course of infection in diverse rodent models. In models of bacterial ( Salmonella typhimurium , Staphylococcus aureus , Klebsiella pneumonia , and Rickettsia typhi ), viral (influenza virus, herpes simplex virus, and rabies virus), and protozoal ( Trypanosoma cruzi ) infection, ambient temperature directly correlates with host responsiveness—lower temperatures leading to impaired immune responses (Moragues and Pinkerton, 1944; Miraglia and Berry, 1962; Previte and Berry, 1962; Underwood et al, 1966; Amrein, 1967; Baetjer, 1968; Previte et al, 1970; Won and Ross, 1971; Bell and Moore, 1974; Jiang et al, 2000; Rice et al, 2005). These effects can be dramatic: in experimental murine typhus, weather-associated changes in ambient laboratory temperature (from 29.4–36.6 to 18.3–22.8°C) shifted mortality rates from 9 to 100% (Moragues and Pinkerton, 1944).…”
Section: Infection Immunity and Thermoneutralitymentioning
confidence: 99%
“…Studies dating back at least to the 1940s indicate that ambient temperature profoundly alters the course of infection in diverse rodent models. In models of bacterial ( Salmonella typhimurium , Staphylococcus aureus , Klebsiella pneumonia , and Rickettsia typhi ), viral (influenza virus, herpes simplex virus, and rabies virus), and protozoal ( Trypanosoma cruzi ) infection, ambient temperature directly correlates with host responsiveness—lower temperatures leading to impaired immune responses (Moragues and Pinkerton, 1944; Miraglia and Berry, 1962; Previte and Berry, 1962; Underwood et al, 1966; Amrein, 1967; Baetjer, 1968; Previte et al, 1970; Won and Ross, 1971; Bell and Moore, 1974; Jiang et al, 2000; Rice et al, 2005). These effects can be dramatic: in experimental murine typhus, weather-associated changes in ambient laboratory temperature (from 29.4–36.6 to 18.3–22.8°C) shifted mortality rates from 9 to 100% (Moragues and Pinkerton, 1944).…”
Section: Infection Immunity and Thermoneutralitymentioning
confidence: 99%
“…The methods used were described in detail in an earlier paper (25). Briefly, Salmonella typhimurium, strain RIA, was grown for 16 to 18 h at 37 C in brain-heart infusion broth (Difco, Detroit, Mich.).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were assayed qualitatively for the presence of Salmonella. The results were presented in an earlier paper (25). A replicate 3-ml sample was frozen at -50 to -70 C and stored at -25 to -30 C for seven days or less prior to quantitative assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies (Miraglia and Berry, 1962;Previte et al, 1970Previte et al, , 1973 showed enhanced Salmonella infection (frequency and persistency) in mice exposed to cold temperature. Tannock and Savage (1974) observed that deprivation of food, water, and bedding for 48 hours caused increased intestinal population levels of Salmonella Typhimurium and coliforms, and reduced levels of lactobacilli, in mice.…”
Section: Rostagnomentioning
confidence: 99%